2014
DOI: 10.1364/boe.5.002978
|View full text |Cite
|
Sign up to set email alerts
|

A high-efficiency fiber-based imaging system for co-registered autofluorescence and optical coherence tomography

Abstract: Abstract:We present a power-efficient fiber-based imaging system capable of co-registered autofluorescence imaging and optical coherence tomography (AF/OCT). The system employs a custom fiber optic rotary joint (FORJ) with an embedded dichroic mirror to efficiently combine the OCT and AF pathways. This three-port wavelength multiplexing FORJ setup has a throughput of more than 83% for collected AF emission, significantly more efficient compared to previously reported fiber-based methods. A custom 900 µm diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Twelve articles described OCT findings regarding healthy oral mucosa. Ridgway et al showed how the OCT image of normal buccal mucosa allows identification of stratified squamous epithelium (SS) along the mucosal surface, the underlying lamina propria (LP), and the transition between these tissues along the basement membrane (BM) boundary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve articles described OCT findings regarding healthy oral mucosa. Ridgway et al showed how the OCT image of normal buccal mucosa allows identification of stratified squamous epithelium (SS) along the mucosal surface, the underlying lamina propria (LP), and the transition between these tissues along the basement membrane (BM) boundary.…”
Section: Resultsmentioning
confidence: 99%
“…However, based on the same basic principles, different devices allow inspection of the tissues with different parameters and different techniques, making comparisons among results obtained by the various research groups difficult. In 13 of the 27 studies, the oral mucosa was examined with a commercial OCT apparatus (seven different types of equipment); the remaining 14 used an OCT system developed by the authors.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional multi-modality systems require multiple sources which increase complexity of the system [4, 9, 20, 21]. Additionally both sources contribute to the ocular maximum permissible exposure (MPE) [14, 15].…”
Section: Pitfalls and Troubleshootingmentioning
confidence: 99%
“…Depending on the kind of tissue being investigated, the imaging contrast provided by OCT might not be sufficient for clinical diagnosis, since it stems solely from single backscattering events and changes in the refractive index. Therefore, it is recommendable to combine OCT with other optical and nonoptical modalities, [7][8][9][10][11] to enable more comprehensive characterization of the tissue properties.…”
Section: Introductionmentioning
confidence: 99%